Cancer nanomedicine: from targeted delivery to combination therapy. Issue 4 (April 2015) - Xu, Xiaoyang; Ho, William; Zhang, Xueqing; Bertrand, Nicolas; Farokhzad, Omid
Highlights Nanomedicine brings new solutions for cancer therapy. Nanomedicine has the potential to target specific cells for chemotherapy. Stealth technology can enhance the circulation half-life and controlled release of therapeutic agents. Drug/RNAi combinatorial strategies show promising synergistic effects.